The Effect of Internet Corpus Learning on Students’ Japanese Learning Motivations and Learning Effect - Shen, Rizhong (Frontiers in Psychology, 2022)
Information education has been vigorously promoted in various countries, making the application of information technologies in language education popular. The combination of information technologies and Japanese learning can make information technologies a practical tool to promote students' thinking and cognitive abilities in Japanese learning. Corpus teaching is a kind of information technologies integrated teaching method, which enables students to carry out meaningful Japanese learning and promotes students' learning performance and learning effect. Based on information education, the Japanese learning method under Internet corpus is constructed and applied to practical teaching. The present work investigates students' learning performance and learning effect through a questionnaire. Through the experimental design, Japanese teaching has been conducted on 322 students in a university in Shanghai for 18 weeks (3h/week) under the experimental Internet corpus. Through the experiment, it is found that the various factors affect the Internet corpus learning method, and the linear relationship between the influencing factors is divided. Through the comparison results, it is also found that the Internet corpus teaching method can have a positive impact on students' learning performance, and then promote their learning effect. The application of Internet corpus learning matches the development of text corpus and audio corpus and the support of picture databases. Audio and video corpora can effectively improve students' learning performance and learning effect by searching for learning content in the database. Suggestions are put forward that the government should optimize its policies to promote Japanese learning and informal education based on learning performance.